2012
DOI: 10.2147/dmso.s26980
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir for the treatment of obese patients with type 2 diabetes

Abstract: Abstract:The risk for developing type 2 diabetes (T2DM) is greater among obese individuals. Following onset of the disease, patients with T2DM become more likely to be afflicted with diabetic micro-and macrovascular complications. Decreasing body weight has been shown to lower glycosylated hemoglobin and improve other metabolic parameters in patients with T2DM. Medications used to lower blood glucose may increase body weight in patients with T2DM and this has been repeatedly shown to be the case for convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Although a small HbA 1c reduction was seen in both groups, a small weight reduction was seen in the TI-Gen2 group, whereas a statistically significant weight gain occurred for the insulin aspart group. Although the mechanism is not known with certainty, reduced concern about hypoglycemia may lead to less "defensive" eating (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although a small HbA 1c reduction was seen in both groups, a small weight reduction was seen in the TI-Gen2 group, whereas a statistically significant weight gain occurred for the insulin aspart group. Although the mechanism is not known with certainty, reduced concern about hypoglycemia may lead to less "defensive" eating (15).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, (14), and preferential inhibition of hepatic glucose production vs. peripheral glucose uptake (19). Our investigation using the obese diabetic db/db mouse model demonstrated that d-INS but not h-INS increased circulating GLP-1 levels, which were associated with decreased weight gain, reduced food intake, and improved glucose homeostasis.…”
Section: Discussionmentioning
confidence: 67%
“…It is noted that d-INS can exert its actions in other tissues or organs to contribute to its weight-sparing effects. One such example is that d-INS increases adiponectin levels, which is associated with both weight loss and reduced food intake in diabetic rats (19). A recent study by Schinner and colleagues (37) has demonstrated that adipocyte-derived Wnt signaling molecules could enhance ␤-cell proliferation and secretion, suggesting that cross talk between Wnt and insulin signaling could occur at intraorgan levels to exert physiological or pathophysiological relevance.…”
Section: Discussionmentioning
confidence: 99%
“…This alteration promotes the binding of DET to blood albumin, which prolongs its life in the circulation and selectively enhances its uptake into hepatic and central nervous system (CNS) tissue (13,25,26). Clinical trials have demonstrated that DET has a significant weight-gain-sparing effect in diabetic patients, in contrast to other long-acting forms of insulin (14,15). However, the mechanism underlying this effect remains unknown.…”
mentioning
confidence: 99%
“…However, the mechanism underlying this effect remains unknown. Among the hypotheses proposed for the weight-sparing effect of DET is the possibility of enhanced CNS catabolic effects of this insulin analog (14,15,23).…”
mentioning
confidence: 99%